Neutrophils: Amoeboid Migration and Swarming Dynamics in Tissues - Mihlan, Michael; Glaser, Katharina M.; Epple, Maximilian W.; Lämmermann, Tim (Frontiers in Cell and Developmental Biology, 2022)
Neutrophils are key cells of our innate immune response with essential roles for eliminating bacteria and fungi from tissues. They are also the prototype of an amoeboid migrating leukocyte. As one of the first blood-recruited immune cell types during inflammation and infection, these cells can invade almost any tissue compartment. Once in the tissue, neutrophils undergo rapid shape changes and migrate at speeds higher than most other immune cells. They move in a substrate-independent manner in interstitial spaces and do not follow predetermined tissue paths. Instead, neutrophil navigation is largely shaped by the chemokine and chemoattractant milieu around them. This highlights the decisive role of attractant-sensing G-protein coupled receptors (GPCRs) and downstream molecular pathways for controlling amoeboid neutrophil movement in tissues. A diverse repertoire of cell-surface expressed GPCRs makes neutrophils the perfect sentinel cell type to sense and detect danger-associated signals released from wounds, inflamed interstitium, dying cells, complement factors or directly from tissue-invading microbes. Moreover, neutrophils release attractants themselves, which allows communication and coordination between individual cells of a neutrophil population. GPCR-mediated positive feedback mechanisms were shown to underlie neutrophil swarming, a population response that amplifies the recruitment of amoeboid migrating neutrophils to sites of tissue injury and infection. Here we discuss recent findings and current concepts that counteract excessive neutrophil accumulation and swarm formation. In particular, we will focus on negative feedback control mechanisms that terminate neutrophil swarming to maintain the delicate balance between tissue surveillance, host protection and tissue destruction.